Effect of Mercuric Nitrate on the Chromosomes of Channa punctatus (Bloch, 1793) - N.P., Ansy Mathew; Jahageerdar, Shrinivas (Fishery Technology, 2025)
The effect of different doses (0.019, 0.038 and 0.075 ppm) of mercuric nitrate on the chromosomes of Channa punctatus was studied. The karyotype was done by standard colchicine, potassium chloride, acetomethanol and air-drying geimsa staining technique. It was observed that the percentage of Total Metaphase spreads with Chromosomal Aberrations (T.M.C.A.) increased with the increasing concentration levels. Mercuric nitrate induced structural chromosomal aberrations included breaks, fragments, dicentric and ring type chromosomes. The study revealed that 120 h of exposure in mercuric nitrate at concentration levels as low as 0.019 ppm induced chromosomal aberrations in fish.